(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Respiratory Tract Infection (RTI) is a very common disease in our country. Bacterial infections in the respiratory tract causing significant morbidity andmortality in hospitalized patients. Information on the prevalence of bacterial infection in RTI in our health care settings is lacking. Moreover, the injudicious use of antibiotics often leads to antibiotic resistance which is an emerging problem. The objective of this study was to determine the prevalence of bacterial infections and antibiotic resistance patterns in pathogens isolated from the sputum samples of admitted patients suffering from RTI in a tertiary care teaching hospital in the Coronavirus Disease (COVID-19) era. Materials and methods: In this cross-sectional study 104 patients who were admitted to the Medicine Department of Chittagong Medical College Hospital with a diagnosis of RTI from February 2021 to June 2021 were included. Bacterial isolates from the sputum culture were confirmed by the standard microbiological methods. Antibiotic resistance was determined by using the disk diffusion method. Results: Out of 104 processed sputum samples 92 (88.5%) cases had established bacterial etiology. Klebsiella (45.2%) was the most common organism followed by Pseudomonas (17.2%) and Acinetobacter (14.4%). In antimicrobial susceptibility testing, Imipenem and meropenem were sensitive against Klebsiella. Ciprofloxacin, levofloxacin, imipenem, meropenem and piperacillin were sensitive against Pseudomonas. Acinetobacter was highly resistant to ceftriaxone. Conclusions: The resistance pattern varied for different organisms. Therefore, appropriate identification of the causative organisms and their antibiotic resistance is crucial for the right choice of antibiotic therapy in LRTIs. JCMCTA 2021 ; 32 (2) : 8-13